Pendidikan Kepemimpinan Guru Sejarah Di Era Globalisasi - Andriana Sofiarini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
ABSTRACT The purpose of this study was to determine the spirit of current teacher leadership and historical teacher leadership education at STKIP PGRI Lubuklinggau in the era of globalization. The research method used is a qualitative method. In this study, researchers used direct observation results with the researchers' own instruments. Researchers with the results of their observations are supported by reference sources trying to analyze, analyze and present data according to what is in the field. The results showed that 1) the spirit of teacher leadership, namely as a prospective history teacher, students must be skilled in self-development when participating in lecture activities both inside and outside the classroom. 2) Teacher leadership education in the era of globalization, namely as candidates for history teachers, students must be able to adapt to the times, be able to develop themselves and continue to hone their abilities as prospective leaders in the era of globalization. The conclusions of this study indicate that the importance of leadership education for prospective history teachers in the era of globalization and being taught as prospective teachers, as well as making a leader who is wise, innovative thinking, and wise who gives birth to leaders in the future. Keywords: Globalization, History, Leadership, Teachers.